Can Personality Traits and Social Support Predict Psychiatric Patient’s Medication Adherence? - OGBONNAYA, Chisom E.; OGINYI, Ronald C.N.; ARINZE, Nwadiogo C.; BINI, Olabode D.; NDUKAIHE, Izuchukwu L.G. (Journal of Psychology and Allied Disciplines, 2025)
Adhering to medication among psychiatric patients may be dependent on personality traits and level of patients’ social support. The study explored personality traits through the big five personality and social support as factors to medication adherence. Through purposive sampling, 250 psychiatric patients (116 males, 134 females) whose age ranged from 22-56 (M = 34.30, SD =7.42), were sampled from a federal teaching hospital in the Southeastern region of Nigeria. Multiple regression was adopted to analyze study data. The result showed that personality and social support positively predicted medication adherence. Specifically, the result showed that openness to experience, agreeableness and neuroticism positively predicted medication adherence, while conscientiousness negatively predicted medication adherence. However, extraversion did not predict medication adherence. The findings highlight importance of understanding personality profiles of patients to foster appropriate mechanism to medication adherence, as well as importance of healthy social support among psychiatric patients to improve medication adherence.